Implementasi Standar Pengelolaan Penelitian: Studi Kasus di IAIN Palangka Raya - Ajahari, Ajahari; Puspita, Puspita; Asmawati, Asmawati; Misbah, Misbah; Arifin, Anwar; Hanafiyah, Hanafiyah; Handayani, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This study aims to describe and analyze the implementation of research management standards which include planning, organizing, implementing, and controlling. The research approach used is descriptive qualitative with the case study method. The research subjects were Vice Rector 1, the Chair and Secretary of LPPM, the Head of the Research Center, and the Head of Planning and Finance of IAIN Palangka Raya. The determination of research subjects was carried out by purposive sampling with data collection techniques through observation, interviews, and documentation. The results of the research show that research management planning activities begin with the preparation of development master plans, strategic plans, and operational plans, preparation of research roadmaps, annual work programs, preparation of Terms of Reference and research budget plans, and the preparation of Research Guidelines. In implementing research management standards, there are 12 stages carried out, including dissemination of technical instructions, research registration, administrative selection, substance selection, determination of nominees, proposal seminars, determination of beneficiaries, preparation of work orders, disbursement of funds, conducting research, monitoring evaluation, review of research outputs, results seminars, and final reports. Efforts to control research activities are carried out with several strategies: making regulations and technical guidelines for research, managing registration and selection of proposals as well as meetings for determining nominees, preparing work orders, managing intermediate seminars, managing presentations of research results, making research logbooks, registering IPR research results, publishing articles research, seeking SPI involvement in research management activities, uploading research reports to Litapdimas, imposing sanctions, preparing research management reports, monitoring and evaluating research management.